Tracking eye movements when solving geometry problems with handwriting devices - John J. H. Lin; Sunny S. J. Lin (Journal of Eye Movement Research)
The present study investigated the following issues: (1) whether differences are evident in the eye movement measures of successful and unsuccessful problem-solvers; (2) what is the relationship between perceived difficulty and eye movement measures; and (3) whether eye movements in various AOIs differ when solving problems. Sixty-three 11th grade students solved five geometry problems about the properties of similar triangles. A digital drawing tablet and sensitive pressure pen were used to record the responses. The results indicated that unsuccessful solvers tended to have more fixation counts, run counts, and longer dwell time on the problem area, whereas successful solvers focused more on the calculation area. In addition, fixation counts, dwell time, and run counts in the diagram area were positively correlated with the perceived difficulty, suggesting that understanding similar triangles may require translation or mental rotation. We argue that three eye movement measures (i.e., fixation counts, dwell time, and run counts) are appropriate for use in examining problem solving given that they differentiate successful from unsuccessful solvers and correlate with perceived difficulty. Furthermore, the eye-tracking technique provides objective measures of students’ cognitive load for instructional designers.